Impact of Brands on Consumer Behaviour. A cross-generation Analysis. - Lukačínová, Michaela; Zlatić, Marija; Lhotáková, Markéta, 1971-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
The aim of this thesis is to determine the impact of brands on consumer behavior, to analyze the depth of correlation between consumers’ perception of a brand and consumers’ final purchases and to highlight the importance and strength of effective strategic management of the brand. A certain part of the paper is also devoted to intergenerational analysis. The examination of these goals is based on the discussion of the key theories and important concepts that stand behind this complex system and their application in today’s world. Secondary data, obtained from several books, various articles, papers and reports, were used for this purpose. Primary data are collected on the basis of individual interviews, where each participant represents a certain generation, with its characteristics, opinions, attitudes and differences. Appropriate conclusions and research results are derived from a combination of all obtained data. In today's dynamically developing world, various changes are taking place. Brand and consumer behavior are no exception. Many successful companies that have built strong brands are aware of this fact and therefore constantly adapt their planning, implementation and management of brand strategy to these changes. Therefore, this thesis offers an insight into the most important aspects that should be taken into account when managing the brand and achieving the goals.
Vedoucí práce: Marija Zlatić
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses